Sustainability of Indonesian Village Fund Policies - Yanhar Jamaluddin, Asep Sumaryana & Budiman Rusli (International Journal of Advanced Science and Technology, 2020)
Political decision and implementation of village fund to support rural communities take the social researchers attentions. Indonesian government policy on village fund needs to study for better management with right target and optimal programs. This research article is intended to seek the factors that might  make sustain of Village Fund policies in Indonesia. A qualitative research design was applied to collect the data; by using the three cycles of analysis, they were actor, impact and factors.  Data obtained shows that; first in actor analysis it shows that the formulating process of Village Fund Policy involves the internal bureaucratic actors. Second, the implementation process puts the Village Government becomes as the benefited actors/institutions and Regency Government becomes the disadvantaged actors/institutions. Last, an impact analysis shows that with their authority, the Village stands alone with its program plans so that the regions difficult to integrate the program. It concludes that the village development programs in Indonesia depends on the public policies that involved the officers, politicians and pressure groups, and it now has not been synchronized with the Middle Term of Planning Development Policy due to actors and impacts analysis.  The sustainability of Village Fund policies is found mostly determined by political factors and the commitment of policy actors, not depends on the well-managed programs.